LOCAL ECONOMIC DEVELOPMENT IN THEORIES OF REGIONAL ECONOMIES AND RURAL STUDIES - Kačar, Bahrija; Curić, Jasmina; Ikić, Selma (Economics of Agriculture, 2016)
In this paper is a detailed analysis of the basics in the theory of economic development during the period from mid last century until today. It states the most significant theories, points out their ranges, offers a critical review regarding their treatment of development, especially regional, rural and local one. It observes those theories according to different classifications existing in scientific literature, primarily the ascend theory, stagnation theory, balanced economic growth theory; then, short-term and long-term development and growth theories; traditional and endogenous theories; economic growth stages theory emphasized after the WW II; structural changes theory; dependency theory, neo-classic counter-revolution theory and endogenous theory as a new growth theory. The analysis becomes wider with a study on development in regional economy theories and rural studies and it systematizes the classification of those theories according to regional economy academics. Distancing ourselves from any particular division as the most suitable and acceptable one, the theories are treated separately and in an historic context, in order to encircle the time framework which from modern theories, dealing with local level development difficulties, resulted. It asserts The Community-led Rural Development Theory, often referred to as the Community Development Theory, or marked as Bottom-up Partnership Approach. The analysis of development theories asserts that mixed exogenous - endogenous approach to development links the rural/local development to the globalization process mostly due to fast technology changes of the IT and communication sectors.